Effects of recasts and prompts on L2 pronunciation development: Teaching English /ɹ/ to Korean adult EFL learners. (August 2016) - Gooch, Reginald; Saito, Kazuya; Lyster, Roy
Abstract: The current study aimed to test how two different types of corrective feedback—recasts and prompts—can differentially affect the pronunciation development of English /ɹ/ by Korean learners in the context of simulated meaning-oriented classrooms receiving form-focused instruction (FFI). Twenty-two Korean learners of English as a foreign language were divided into three groups (FFI-only, FFI-recasts, FFI-prompts). Each group received 4 h of instruction in which they were taught how to structure an argument in English through activities designed to simultaneously focus their attention on /ɹ/, including explicit articulatory instruction. All lessons were video-recorded, which allowed all instances of feedback and learner response to be identified and coded. Production was measured through both spontaneous and controlled tests, and judged by five trained English native-speaking listeners. According to the results of the pre/post-tests, recasts were especially helpful in the improvement of controlled production of /ɹ/, whereas prompts were facilitative of not only controlled but also spontaneous production of /ɹ/. The results of the video-coding analysis further demonstrated that, during instruction, students were pushed by prompts to improve intelligibility mainly through the adjustment of interlanguage strategies (e.g., prolonging the phonemic length), and by recasts to refine accuracy in their /ɹ/ production.